Our Homes: Home and Independence Project - Garcia Iriarte, Edurne (My University, 2015)
This book is about a research project we did to learn what it was like for people with intellectual disabilities in Ireland to move from one home to another.
PUBLISHED
Dublin; Limerick; Galway
Keywords: Inclusive Society; Community living; Human Rights; INTELLECTUAL DISABILITY; IRELAND; Inclusive research